The effectiveness of an innovation ecosystem formation as territory strategic development element - I. V. Korchagina; O. V. Sychjova-Peredero (Управление)
The problem of assessing and justifying the cost-effectiveness of creating various elements of an innovation ecosystem of territories, in particular, regions has been analyzed in the article. Most of the constituent entities of the Russian Federation are working on the formation of innovative ecosystems in the context of strategic economic management. However, this raises the issue of budget and economic cost-effectiveness. The purpose of the article is to develop a methodological approach and the main directions of determining the effectiveness of the formation of innovative ecosystems.It has been shown, that it is incorrect to evaluate efficiency only by the direct budget effect. Based on expert interviews the main effects of the development of the region’s innovation ecosystem have been identified and classified. It has been allowed us to clarify specific areas of the influence of the innovation ecosystem on a number of economic indicators, including the gross regional product. The formulas for calculating the most important effects of the development of innovative ecosystems in terms of value have been proposed. The influence of innovation ecosystems on the achievement of public goals of socio-economic development of territories has been noted. Based on data on the development of an innovation ecosystem with a core in the form of a regional support university and the implementation of student entrepreneurial projects, key effects arising from costs from various sources have been identified.It has been shown, that additional costs for the development of innovative ecosystems can be fully justified, provided that a full-fledged funnel of projects is implemented. Attention has been paid to the problem of more complete and accurate assessments of the long-term effects of the development of an innovation ecosystem for spatial significance, migration attractiveness, and the development of human capital of the territory. Conclusions about the significant impact of costs on the formation of an innovation ecosystem on the development of the territory (both existing and potential) have been made.